2012
DOI: 10.1007/s00484-012-0558-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of future warming on winter chilling in Australia

Abstract: Increases in temperature as a result of anthropogenically generated greenhouse gas (GHG) emissions are likely to impact key aspects of horticultural production. The potential effect of higher temperatures on fruit and nut trees' ability to break winter dormancy, which requires exposure to winter chilling temperatures, was considered. Three chill models (the 0-7.2°C, Modified Utah, and Dynamic models) were used to investigate changes in chill accumulation at 13 sites across Australia according to localised temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Gabaldón-Leal et al (2017) used an adapted version of the de Melo-Abreu model to calculate the projected chilling units for olive trees in the Andalusia region, also showing a generalised decrease in chilling accumulation projected for the rest of the century. Our work has findings similar to those of other studies performed in other parts of the globe; for example, Darbyshire et al (2013), who analysed the impact of the future warming on winter chilling in Australia, concluded that adaptation will be necessary in many locations, at least to some extent, within the next 50 years. Also, a negative impact of climate change on chilling accumulation was found, as expected, in another region with Mediterranean climate, California, in Luedeling et al (2009a), showing that adaptation would be difficult for some crops under some scenarios.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Gabaldón-Leal et al (2017) used an adapted version of the de Melo-Abreu model to calculate the projected chilling units for olive trees in the Andalusia region, also showing a generalised decrease in chilling accumulation projected for the rest of the century. Our work has findings similar to those of other studies performed in other parts of the globe; for example, Darbyshire et al (2013), who analysed the impact of the future warming on winter chilling in Australia, concluded that adaptation will be necessary in many locations, at least to some extent, within the next 50 years. Also, a negative impact of climate change on chilling accumulation was found, as expected, in another region with Mediterranean climate, California, in Luedeling et al (2009a), showing that adaptation would be difficult for some crops under some scenarios.…”
Section: Discussionsupporting
confidence: 90%
“…The de Melo-Abreu et al (2004) model, consisting in a generalisation and simplification of the Utah model applied to olive trees, showed good performance. Model development was based on 15 olive cultivars grown in four locations (Cordoba and Mas Bové in Spain and Santarém and Elvas in Portugal).…”
Section: Chilling Modellingmentioning
confidence: 99%
“…[84][85][86][87] Some are based on the ensemble mean response, 92,114 but others incorporate a range of futures. 71 Those studies with a large number of model runs demonstrate overlapping uncertainty bands between ΔT g increments, as shown in Figure 5, from James et al, 91 based on four ensembles of climate models. This highlights the importance of risk assessment to establish whether there are detectable distinctions between half degree increments in spite of model uncertainty.…”
Section: Inter-model Variabilitymentioning
confidence: 90%
“…Recently, there has been a growing concern about the effect of declining chilling on temperate woody species due to climate warming and the serious lack of mechanistic understanding of the environmental, physiological, molecular, and genetic basis of dormancy (Chuine, 2010;Atkinson et al, 2013;Campoy et al, 2013;Darbyshire et al, 2013;Pope et al, 2013).…”
Section: Discussionmentioning
confidence: 99%